Metabolic Regulation of Two pksCT Gene Transcripts in Monascus ruber Impacts Citrinin Biosynthesis - Yi He; Lisha Zhu; Xingxing Dong; Aoran Li; Suyin Xu; Liling Wang; Yanchun Shao (Journal of Fungi, 2023)
Citrinin (CIT), a secondary metabolite produced by the filamentous fungi Monascus species, exhibits nephrotoxic, hepatotoxic, and carcinogenic effects in mammals, remarkably restricting the utilization of Monascus-derived products. CIT synthesis is mediated through the pksCT gene and modified by multiple genetic factors. Here, the regulatory effects of two pksCT transcripts, pksCTα, and pksCTβ, generated via pre-mRNA alternative splicing (AS), were investigated using hairpin RNA (ihpRNA) interference, and their impact on CIT biosynthesis and the underlying mechanisms were assessed through chemical biology and transcriptome analyses. The CIT yield in ihpRNA-pksCTα and ihpRNA-pksCT (α + β) transformants decreased from 7.2 μg/mL in the wild-type strain to 3.8 μg/mL and 0.08 μg/mL, respectively. Notably, several genes in the CIT biosynthetic gene cluster, specifically mrl3, mrl5, mrr1, and mrr5 in the ihpRNA-pksCT (α + β) transformant, were downregulated. Transcriptome results revealed that silencing pksCT has a great impact on carbohydrate metabolism, amino acid metabolism, lipid metabolism, and AS events. The key enzymes in the citrate cycle (TCA cycle) and glycolysis were significantly inhibited in the transformants, leading to a decrease in the production of biosynthetic precursors, such as acetyl-coenzyme-A (acetyl-coA) and malonyl-coenzyme-A (malonyl-coA). Furthermore, the reduction of CIT has a regulatory effect on lipid metabolism via redirecting acetyl-coA from CIT biosynthesis towards lipid biosynthesis. These findings offer insights into the mechanisms underlying CIT biosynthesis and AS in Monascus, thus providing a foundation for future research.